The Impact of the CAMEL Bank Rating System on Stock Trading Valume: Applied Research (Journal of Accounting and Financial Studies ( JAFS ), 2025)
This research aims to evaluate the banks under study by identifying their strengths and weaknesses using the banking evaluation system (CAMEL), which in turn consists of its five elements: capital adequacy, asset quality, profitability management and liquidity, in addition to measuring the extent to which the banking evaluation system (CAMEL) contributes to increasing or decreasing the volume of stock trading in the stock market of the banks under study. Economic growth does not occur without the presence of financial markets, which play a role in moving the wheel of the economy, as savings units meet investment units, which in turn depend mainly on the stock trading process. The research problem was diagnosed by the question: What is the extent to which the banking evaluation system (CAMEL) contributes to the volume of stock trading? The research adopted the descriptive, analytical and standard approach to the financial data of the banks under study for the years (2014 -2023). The research was applied to two commercial banks listed on the Iraq Stock Exchange, namely (Bank Baghdad and Ashur Bank), and both the statistical program (SPSS) and the program (Excel) were adopted in analyzing the data, and the evaluation of the banks studied was extracted by calculating the indicators of each of its five elements, in addition to measuring the volume of stock trading based on the index of the value of traded shares. The research found that there was fluctuation in the evaluation of the banks studied during the years of the research sample, which in turn affects the volume of stock trading in the Iraq Stock Exchange.